Reconstructing the Self: Trauma and Identity in Frankenstein in Baghdad - Al Mahfoodh, Abdulrahman Dheyaa Nori; Benny, N. Solomon (South Asian Journal of Social Sciences and Humanities, 2025)
This paper investigates trauma traces and reconstructing the self in Frankenstein in Baghdad.  As the aftermaths of war do not end when it stops, its consequences should be traced and dealt  with, especially the psychological effects. Ahmed Saadawi’s Frankenstein in Baghdad (2018)  gives this psychological ruin a body: the Whatsitsname, a conscious corpse sewed together  from Baghdad’s bomb victims. More than a literary device, this creature embodies trauma  transformation in people to make them archives of violence, carrying physical proof of wounds  that would never easily heal. Hence, paper explores how Saadawi’s novel redefines the  common understanding of the Iraqi war aftermath, revealing how collective suffering reformats  both individual psyches and national identity. Moving beyond Western trauma models that  prioritize "recovery narratives," the analysis demonstrates how Iraq’s particular history of  colonialism, sanctions, and occupation demands alternative frameworks. The Whatsitsname’s  cyclical violence—targeting both criminals and onlookers—mirrors the real-world  impossibility of moral attitudes in war areas. Its very existence challenges simplistic divisions  between victims and monsters, suggesting that in war’s moral vacuum, these categories  collapse into one another. So, Frankenstein in Baghdad forces us to confront the unavoidable  truth which says: the distance between "us" and "monsters" is never such long as we pretend.  By giving shape and name to war invisible psychological wounds, Saadawi creates not just a  masterpiece of Iraqi literature, but a vital narrative in world literature about trauma, memory,  and the price of survival.
Keywords: Frankenstein; Reconstructing the Self; Iraq War; Trauma; Identity